An Assessment of Heavy Metals Toxicity in Asian Clam, Corbicula fluminea, from Mekong River, Pa Sak River, and Lopburi River, Thailand - Ai Yin Sow; Koh Han Dee; Seong Wei Lee; Aweng A. L. Eh Rak (The Scientific World Journal)
High population density and economic development attributing to the changes in water quality in Pa Sak River, Lopburi River, and Mekong River have attracted great attention. This research aimed to determine the pollution of heavy metals in collected clams at three different study sites. Bioaccumulation of heavy metals in Asian clam (Corbicula fluminea) may be likely to cause serious health effects on human beings. The clams sampled from three different rivers (Mekong, Pa Sak, and Lopburi) from Thailand were analyzed for the presence of heavy metals (Zn, Cu, Cd, Cr, Mn, and Pb) with an air-acetylene flame atomic absorption spectrophotometer (AAS). Among the heavy metals studied, Zn was recorded as having the highest concentration (127.33-163.65 μg/g) among the three rivers. The observed mean concentration of Cu was in the range of 84.61-127.15 μg/g followed by Mn (13.96-100.63 μg/g), Cr (5.79-15.00 μg/g), Pb (3.43-8.55 μg/g), and Cd (0.88-1.95 μg/g). Overall, Asian clam from Pa Sak River was found to contain high concentrations of Zn, Cu, Cd, Cr, and Pb compared to Mekong and Lopburi River.